2018
DOI: 10.1371/journal.pone.0195978
|View full text |Cite
|
Sign up to set email alerts
|

ST waveform analysis for monitoring hypoxic distress in fetal sheep after prolonged umbilical cord occlusion

Abstract: IntroductionThe inconclusive clinical results for ST-waveform analysis (STAN) in detecting fetal hypoxemia may be caused by the signal processing of the STAN-device itself. We assessed the performance of a clinical STAN device in signal processing and in detecting hypoxemia in a fetal sheep model exposed to prolonged umbilical cord occlusion (UCO).MethodsEight fetal lambs were exposed to 25 minutes of UCO. ECG recordings were analyzed during a baseline period and during UCO. STAN-event rates and timing of epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…[13][14][15][16] Because the NI-fECG uses multiple leads, one of the limitations of STAN, which only uses a single lead scalp electrode, is avoided. [17][18][19] To conclude, NI-fECG for FHR monitoring is a promising technique that is noninvasive, is patientfriendly, and provides accurate information. Future studies should focus on evaluating and improving signal quality of the NI-fECG, especially during the second stage of labor.…”
Section: General Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16] Because the NI-fECG uses multiple leads, one of the limitations of STAN, which only uses a single lead scalp electrode, is avoided. [17][18][19] To conclude, NI-fECG for FHR monitoring is a promising technique that is noninvasive, is patientfriendly, and provides accurate information. Future studies should focus on evaluating and improving signal quality of the NI-fECG, especially during the second stage of labor.…”
Section: General Remarksmentioning
confidence: 99%
“…In contrast to STAN, the NI-fECG provides a multilead fetal ECG and therefore may overcome the current shortcomings in ST waveform analysis. [17][18][19] NI-fECG is not a new technique, as first recordings were made in the early 1900s. 20 However, difficulties in acquiring and processing the electrophysiologic signals limited the development of this technique.…”
mentioning
confidence: 99%
“…In our recent paper " ST waveform analysis for monitoring hypoxic distress in fetal sheep after prolonged umbilical cord occlusion " [1], we concluded that the performance of the STAN device in clinical practice is potentially limited by high false-negative and high false-positive STAN-event rates and loss of ST waveform assessment capacity during severe hypoxemia. This conclusion evoked comments by Kjellmer, Lindecrantz and Rosén that can be summarized as follows: 1) STAN analysis is based on a unipolar lead but the authors used a negative aVF lead, and they did not validate this methodology; 2) The fetuses used in the study were too young to display the signals that the authors were trying to detect.…”
Section: Introductionmentioning
confidence: 99%
“…In their paper, Andriessen at al present a validation of fetal ECG analysis and the clinical STAN device in midgestation fetal lambs exposed to 25 minutes of umbilical cord occlusion [1]. The study presents results that contrast remarkably from previously published experimental data which raises a number of questions and comments.…”
Section: Introductionmentioning
confidence: 99%